How Selection Over Time Contributes to the Inconsistency of the Association Between Sex/Gender and Cognitive Decline Across Cognitive Aging Cohorts. Issue 3 (14th September 2021) - Rouanet, Anaïs; Avila-Rieger, Justina; Dugravot, Aline; Lespinasse, Jérémie; Stuckwisch, Rachel; Merrick, Richard; Anderson, Emma; Long, Leann; Helmer, Catherine; Jacqmin-Gadda, Hélène; Dufouil, Carole; Judd, Suzanne; et al.
Abstract: The association between sex/gender and aging-related cognitive decline remains poorly understood because of inconsistencies in findings. Such heterogeneity could be attributable to the cognitive functions studied and study population characteristics, but also to differential selection by dropout and death between men and women. We aimed to evaluate the impact of selection by dropout and death on the association between sex/gender and cognitive decline. We first compared the statistical methods most frequently used for longitudinal data, targeting either population estimands (marginal models fitted by generalized estimating equations) or subject-specific estimands (mixed/joint models fitted by likelihood maximization) in 8 studies of aging: 6 population-based studies (the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) Study (1996–2009), Personnes Âgées QUID (PAQUID; 1988–2014), the Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study (2003–2016), the Three-City Study (Bordeaux only; 1999–2016), the Washington Heights-Inwood Community Aging Project (WHICAP; 1992–2017), and the Whitehall II Study (2007–2016)) and 2 clinic-based studies (the Alzheimer's Disease Neuroimaging Initiative (ADNI; 2004–2017) and a nationwide French cohort study, MEMENTO (2011–2016)). We illustrate differences in the estimands of the association between sex/gender and cognitive decline in selected examples and highlight the critical role of differential selection by dropout and death. Using the same estimand, we then contrast the sex/gender–cognitive decline associations across cohorts and cognitive measures suggesting a residual differential sex/gender association depending on the targeted cognitive measure (memory or animal fluency) and the initial cohort selection. We recommend focusing on subject-specific estimands in the living population for assessing sex/gender differences while handling differential selection over time.